Peluang dan Tantangan Pengembangan Pelabuhan Sabang Dalam Kebijakan Maritim Nasional - Fahlevi, Reza; Latif, Ikhwan Rahmatika; Aziz, Chairul Iqbal; Khalisni, Khalisni; Akbar, Arif (Universitas Negeri Gorontalo, 2025)
In global maritime context, Indonesia has a strategic position as an archipelagic country. As is known, Indonesia has potential in the fields of fisheries and maritime affairs, so based on this, national maritime policy is needed as the main foundation. This study aims to analyze opportunities and challenges developing Sabang port in the national maritime policy. The research method used in this writing adopts qualitative research method. The findings of the study are that in developing Sabang port there are several opportunities including the utilization Special Economic Zone, as center for trade and logistics, development tourism sector, the creation of government programs such as sea tolls, and strategic position in Strait of Malacca. Furthermore, the challenges faced in developing Sabang port in the national maritime policy are regional security and stability, the creation of environmental and social issues, competition with other ports, transportation connectivity, and infrastructure limitations.